Identification of Community- and Hospital Pulmonary Bacterial Infection Using Culture and PCR Panel in COVID-19 - Ronal Winter; Adhi Kristianto Sugianli; Ida Parwati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
Co-infection or secondary infection is associated with a worse outcome in COVID-19. Information concerning the distribution of pathogenic microbes in COVID-19 has yet to be widely studied. This study aims to evaluate the distribution of bacterial infection in COVID-19, detected using conventional culture and molecular methods. This study was conducted in March-May 2021 in Dr. Hasan Sadikin General Hospital, with a study population of moderate, severe, and critical COVID-19 patients. Microorganisms were identified and analyzed from expectorant sputum or Endotracheal tube aspirates using conventional culture methods (VITEK 2 Compact) and multiplex PCR pneumonia panel (Biofire). Data was presented in a table and figures to describe the organism profile among the two methods. From the 450 COVID-19 patients, 59 subjects were included. The positivity rate of microbial identification reached 79.7% in both methods, dominated by Gram-negative bacteria for both community and hospital-acquired infections. The pathogens most frequently detected using conventional methods and multiplex PCR were Acinetobacter baumanii (15.3%; 23.7%) and Klebsiella pneumoniae (23.7%; 28.8%). The multiplex PCR method detected Haemophilus influenzae (15.3%) and respiratory viruses (3.4%), which conventional methods could not detect. Gram-negative bacteria were the most frequent pathogen in COVID-19 in both populations. The multiplex PCR method has the advantage due to its shorter examination time. The application of both methods helps determine antibiotic therapy for COVID-19. Both methods identified Klebsiella pneumoniae and Acinetobacter baumanii as the dominant bacteria in both populations. This study helps establish antibiotic management in COVID-19, thus preventing antibiotic resistance.